Rancang Bangun Sistem Informasi Penilaian Kinerja Badan Usaha Milik Negara Pada PT. SUCOFINDO - Yanuar Affandy; Haryanto Tanuwijaya; Mochammad Arifin (Jurnal Sistem Informasi Universitas Dinamika, 2016)
PT. SUCOFINDO is one of the state-owned company engaged in the inspection, supervision, assessment and testing of the first in Indonesia. At this time for assessment of performance at PT. SUCOFINDO guided by the Ministerial Decree No. KEP-100 / MBU / 2002 which consisted of an assessment of financial and non-financial aspects however, the company still difficulties in applying the guidelines of this Decree, as long as the company's performance measurement is focused on the financial aspect alone, for measurement of non-financial aspects are difficulties in implementing data collection operations, due to the lack of parts that run it. As a result, less measurable results reflect the achievement of actual results of company performance. In addition, assessment of performance running now is end-system or system will end by issuing a single value, the system is not able to provide details of assessment that contains information about the condition of the company now. Therefore, it is expected by the information system of performance appraisal can help PT. SUCOFINDO in assessing the performance and non-financial aspects of finance in accordance with Government requirements listed in the Ministry of State-Owned Enterprises